Mesenchymal-Stem-Cell–Derived Extracellular Vesicles Mitigate Trained Immunity in the Brain - Feng, Yiwei; Guo, Min; Zhao, Hongchen; Han, Sida; Dong, Qiang; Cui, Mei (Frontiers in Bioengineering and Biotechnology, 2020)
Trained immunity was recently discovered in innate immune cells and shown to facilitate the clearance of pathogens at the time of occurrence of the second insult. However, it exacerbates several aspects of neuropathologies, and proper therapy is needed to rectify this abnormal immune reaction. Mesenchymal-stem cells (MSCs) exhibit a distinct capability for brain repair but are associated with safety concerns. Extracellular vesicles derived from MSCs are a promising alternative therapy. In this study, we used lipopolysaccharides to activate trained immunity in the brain and examined the therapeutic potential of MSC-derived extracellular vesicles in mitigating the trained-immunity-induced exacerbated neuropathology. We found that MSC-derived extracellular vesicles showed comparable effects to those of MSCs in the mitigation of trained immunity in the brain. Moreover, the administration of MCS-derived extracellular vesicles mitigated the aggregated inflammatory responses in the acute stage of stroke and alleviated the trained-immunity-induced increased load of amyloid-β in APP/PS1 mice. We further investigated the molecular machinery of MSC-derived extracellular vesicles and found that IL-10 is important for the mediation of the therapeutic potential of MSC-derived extracellular vesicles toward the alleviation of trained immunity. Our study indicates that extracellular-vesicle-based regenerative strategies might be useful to mitigate trained immunity in the brain.